LEGAL MECHANISMS FOR ENSURING PRIVACY IN THE USE OF ARTIFICIAL INTELLIGENCE (World Bulletin of Management and Law, 2023)
Legal mechanisms for ensuring privacy in the use of artificial intelligence, the widespread introduction of AI technologies in the life of our society, and the need to carry out scientific research on ensuring the privacy of citizens living in our country. Therefore, it is necessary to study and analyze the concept of the right to privacy from a conceptual, scientific and methodological point of view
Keywords: Digitization; personal; privacy; protection from interference with personal life